ANALISIS KEBIJAKAN PENDANAAN PT BANK DANAMON INDONESIA, TBK DAN ANAK PERUSAHAAN - FRISKA ARTARIA SITANGGANG (Jurnal Manajemen Terapan dan Keuangan, 2016)
The title of this research “ funding policy analysis of PT Bank Danamon Indonesia, Tbk and subsidiaries”.  The main objective of this study was to analyze the description of the funding policy at PT Bank Danamon Indonesia, Tbk and subsidiaries, and to know whether the finance post which contributes more dominant in the published financial statement of the bank against its funding policy. The research methods used in this research is the study of literature and secondary data. Based on the financial information presented in the annual financial statement of banks in this case common size analysis and time series analysis of comparative ratios; leverage ratio, the value of firm, and profitability, and perform calculations on the weighted average cost of capital (wacc) at the bank. The results showed that the description of the funding policy of PT Bank Danamon Indonesia, Tbk and subsidiaries for the period 2011-2015, is more dominated by the use of debt but equity will remain a source of funding in their businness activities. During the period of the study note that the policy of optimal capital structure that in 2012 it was supported by the data shown consistent with the theory that underlies this study where indicated by the condition of capital structure, the Bank was able to increase its value of firm, lower cost of capital, and improve profitability.